Perceiving AI as labor-replacing reduces democratic legitimacy and political engagement - Armin Granulo; Andreas Raff; Christoph Fuchs (Proceedings of the National Academy of Sciences, 2026)
AI is expected to reshape society and labor markets, yet experts remain divided on whether AI will primarily displace human labor or generate new employment opportunities. Despite the importance of this debate, little is known about how the public perceives AI’s labor market impact—and how these perceptions affect democratic attitudes and behaviors. Large-scale survey data ( N = 37,079; 38 European countries) indicate that the public tends to view AI as labor-replacing rather than labor-creating. Controlling for technology-related, political, and sociodemographic factors, these data further show that perceiving AI as labor-replacing (vs. labor-creating) is associated with lower satisfaction with democracy and political engagement with technology. Two preregistered, nationally representative experiments ( N = 1,202, United Kingdom; replication study N = 1,200, United States) provide causal evidence for this relationship. Participants exposed to a labor-replacing (vs. labor-creating) AI frame report greater erosion of trust in democracy and lower willingness to politically engage with future AI developments. Together, our findings suggest that perceptions about AI’s labor market consequences—regardless of actual outcomes—may decrease democratic legitimacy and public engagement in shaping the future of AI.